Short-course performance variation across all race sections: How 100 and 200 m elite male swimmers progress between rounds - Francisco Cuenca-Fernández; Jesús J. Ruiz-Navarro; Marek Polach; Marek Polach; Raúl Arellano; Dennis-Peter Born; Dennis-Peter Born (Frontiers Media S.A., 2023)
IntroductionTo investigate performance variation in all race sections, i.e., start, clean swimming, and turns, of elite short-course races for all swimming strokes and to determine the effect of performance variation on race results.MethodsComparing finalists and non-qualified swimmers, a total of 256 races of male swimmers (n = 128, age: 23.3 ± 3.1, FINA points: 876 ± 38) competing in the European short-course swimming championships were analyzed. The coefficient of variation (CV) and relative change in performance (Δ%) were used to compare intra-individual performance progression between rounds and inter-individual differences between performance levels using a linear mixed model.ResultsWhile most performance variables declined during the races (P < 0.005), performance was better maintained in 200 m compared to 100 m races, as well as in finalists compared to non-qualified swimmers. In 100 m races, Start Times improved between heats, semi-finals, and finals (P < 0.005) and contributed to the improved Split Times of Lap 1 in freestyle (P = 0.001, Δ = −1.09%), breaststroke (P < 0.001; Δ = −2.48%), and backstroke (P < 0.001; Δ = −1.72%). Swimmers increased stroke rate from heats/semi-finals to finals in freestyle (P = 0.015, Δ = 3.29%), breaststroke (P = 0.001, Δ = 6.91%), and backstroke (P = 0.005; Δ = 3.65%). Increases in stroke length and clean-swimming speed were only significant between rounds for breaststroke and backstroke (P < 0.005). In 200 m races, Total Time remained unchanged between rounds (P > 0.05), except for breaststroke (P = 0.008; CV = 0.7%; Δ = −0.59%). Start (P = 0.004; Δ = −1.72%) and Split Times (P = 0.009; Δ = −0.61%) only improved in butterfly. From the turn variables, OUT_5 m times improved towards the finals in breaststroke (P = 0.006; Δ = −1.51%) and butterfly (P = 0.016; Δ = −2.19%). No differences were observed for SR and SL, while clean-swimming speed improved between rounds in breaststroke only (P = 0.034; Δ = 0.96%).DiscussionPerformance of finalists progressed between rounds in 100 m but not 200 m races, most probably due to the absence of semi-finals. Progression in 100 m races was mainly attributed to improved Start and Split Times in Lap 1, while turn performances remained unchanged. Within round comparison showed higher performance maintenance in 200 m compared to 100 m events, which showed more pronounced positive pacing. Success of finalists was attributed to their overall higher performance level and superior progression between rounds.